Approaches to synthesis of ([1,2,4]triazolo[1,5-c]quinazolin-2-yl)benzoic acids as potential anti-inflammators - Красовська, Н. І. (Farmacevtičnij žurnal, 2022)
Despite their high efficacy NSAIDs have significant side effects due to non-selective inhibition of COX-1 and COX-2. Due to this, medical chemists still pay considerable attention to their design and synthesis, in particular the creation of hybrid molecules that combine in their structure a fragment with anti-inflammatory activity and the quinazoline heterocycle. The aim of the present study is to develop methods for the synthesis of [1,2,4]triazolo[1,5-c]quinazolin-2-yl)benzoic acids as potential anti-inflammatory agents. Quinazolin-4(3H)-ylidene)hydrazides (hydrazones) of benzenedicarboxylic acids, their esters, products of their heterocyclization and nucleophilic degradation were the subjects of the study. The structure of the synthesized compounds was confirmed by elemental analysis and NMR spectroscopy. Anti-inflammatory activity was studied in a model of acute aseptic inflammation («carrageenan test») in rats. Possibilities and limitations of synthesis of [1,2,4]triazolo[1,5-c]quinazolin-2-yl)benzoic acids and their esters via heterocyclization of the corresponding hydrazides and hydrazones oxidative cyclization are shown. It was found that the hydrolysis of 4-[(1,2,4]triazolo[1,5-c]quinazolin-2-yl)benzoic acid esters is not a preparative method for the synthesis of the target acids, due to the hydrolytic cleavage of the pyrimidine cycle. Compounds 3, 4 and 6 with moderate anti-inflammatory activity have been identified, which can be used for further structural modification. Conclusions. It was found that quinazolin-4(3H)-ylidene)hydrazides (hydrazones) of benzenedicarboxylic acids and their esters under the conditions of heterocyclization and oxidative cyclization form [1,2,4]triazolo[1,5-c]quinazolin-2-yl)benzoic acids and their esters. The synthesized compounds are carriers of anti-inflammatory activity and promising for further research.